Formulation of Liposome for topical delivery of arbutin - Wen, Ai-Hua; Choi, Min-Koo; Kim, Dae-Duk (Archives of pharmacal research, 2006)
The aims of this study were to encapsulate arbutin (AR) in liposome to enhance the skin-whitening activity, and to investigate the effect of liposome formulation on the entrapment efficiency (EE%), skin permeation rate and skin deposition. The liposomes were prepared by a film dispersion method with several different formulations and were separated from the solution by using the gel-filtration method. The physical (size distribution, morphology) and chemical (drug entrapment efficiency, hairless mouse skin permeation and deposition) properties of liposomes were characterized. The entrapment efficiency in all liposome formulations varied between 4.35% and 17.63%, and was dependent on the lipid content. The particle sizes of liposomes were in the range of 179.9-212.8 nm in all liposome formulations. Although the permeation rate of AR in the liposome formulations decreased compared with AR solution, the deposition amount of AR in the epidermis/dermis layers increased in AR liposomal formulation. These results suggest that liposomal formulation could enhance the skin deposition of hydrophilic skin-whitening agents, thereby enhancing their activities.